2014
DOI: 10.1055/s-0034-1383037
|View full text |Cite
|
Sign up to set email alerts
|

Skullcap and Germander: Preventing Potential Toxicity through the Application of Hyperspectral Imaging and Multivariate Image Analysis as a Novel Quality Control Method

Abstract: Scutellaria lateriflora (skullcap) is a medicinal herb that has a long history of use in the treatment of ailments such as insomnia and anxiety. Commercial herbal formulations claiming to contain S. laterifolia herba have flooded the consumer markets. However, due to intentional or unintentional adulteration, cases of hepatotoxicity have been reported. Possible adulteration with the potentially hepatotoxic Teucrium spp., T. canadense and T. chamaedrys has been reported. In this study, hyperspectral imaging in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The non-destructive differentiation of raw materials/species to ensure the authenticity of raw material included in herbal products has been investigated [13,22,26]. Quantitatively, although not as accurately as other conventional techniques such as chromatography, adulteration has been successfully detected in commercial products using this technique [30,31]. As far as herbal teas are concerned, the use of HSI in their quality control is fairly new with only a few studies documented.…”
Section: Discussionmentioning
confidence: 99%
“…The non-destructive differentiation of raw materials/species to ensure the authenticity of raw material included in herbal products has been investigated [13,22,26]. Quantitatively, although not as accurately as other conventional techniques such as chromatography, adulteration has been successfully detected in commercial products using this technique [30,31]. As far as herbal teas are concerned, the use of HSI in their quality control is fairly new with only a few studies documented.…”
Section: Discussionmentioning
confidence: 99%
“…(Germander), T . canadense and T. chamaedrys , as well as different species from the same genus Scutellaria has been reported since the early 1990s [ 119 , 258 , 259 , 260 ]. The genus Teucrium also belongs to the same family Lamiaceae and has high morphological similarities with Scutellaria ( Figure 7 ).…”
Section: Dna Barcoding—lessons From the Lamiaceaementioning
confidence: 99%
“…chamaedrys ) were the phenylethanoids, verbascoside and teucrioside. The phenylethanoid marker was suggested to distinguish between the two genera [ 245 , 259 , 263 , 264 , 265 , 266 ]. However, these methods require expert analysts and are time consuming.…”
Section: Dna Barcoding—lessons From the Lamiaceaementioning
confidence: 99%
“…(3) The 621 literature results obtained above are analyzed in this review. Their research objects included grain crops, vegetables, fruit trees, medicinal materials, tobacco, and other crops [14][15][16][17][18][19][20]. Among them, it was found that wheat disease identification attracted the most attention from scientists, with 174 articles in total.…”
Section: Literature Overviewmentioning
confidence: 99%